2013
DOI: 10.1016/j.virol.2013.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of four human adenovirus type 4 genomes reveals molecular evolution through two interspecies recombination events

Abstract: Computational analysis of human adenovirus type 4 (HAdV-E4), a pathogen that is the only HAdV member of species E, provides insights into its zoonotic origin and molecular adaptation. Its genome encodes a domain of the major capsid protein, hexon, from HAdV-B16 recombined into the genome chassis of a simian adenovirus. Genomes of two recent field strains provide a clue to its adaptation to the new host: recombination of a NF-I binding site motif, which is required for efficient viral replication, from another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 87 publications
(156 reference statements)
2
77
0
3
Order By: Relevance
“…Similarly, HAdV-D67 was identified as a recombinant between HAdV-D9, -D25, -D26, -D33, and -D46 (46,55). Recent data provide evidence for the occurrence of recombination between different HAdV species, and even between HAdVs and SAdVs (56,57). Computational analysis of HAdV-E4, the only representative of species E, indicated that this virus is of zoonotic origin and evolved through two interspecies recombination events with lateral partial gene transfer.…”
Section: Current Status Of Hadv Types and Evolution Of Human Adenovirmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, HAdV-D67 was identified as a recombinant between HAdV-D9, -D25, -D26, -D33, and -D46 (46,55). Recent data provide evidence for the occurrence of recombination between different HAdV species, and even between HAdVs and SAdVs (56,57). Computational analysis of HAdV-E4, the only representative of species E, indicated that this virus is of zoonotic origin and evolved through two interspecies recombination events with lateral partial gene transfer.…”
Section: Current Status Of Hadv Types and Evolution Of Human Adenovirmentioning
confidence: 97%
“…Computational analysis of HAdV-E4, the only representative of species E, indicated that this virus is of zoonotic origin and evolved through two interspecies recombination events with lateral partial gene transfer. HAdV-E4 contains 97% of a SAdV-E26-like ge- nome chassis with a hexon containing the L1 and L2 regions from a HAdV-B16-like virus, which may provide compatibility with the new host (57). Adaptation of the virus to the new host could also be related to the acquirement of an NF-1 binding site motif, which is required for efficient viral replication, in a further recombination event.…”
Section: Current Status Of Hadv Types and Evolution Of Human Adenovirmentioning
confidence: 99%
“…between members of different AdV species has also been reported, either between AdVs of the same primate host or of different primate hosts. Dehghan and coworkers showed that HAdV-4, the sole human member of species HAdV-E, originates from recombination of a domain of the hexon gene (encoding the major capsid protein) of HAdV-16 (species HAdV-B) into the genome of a member of species HAdV-E isolated from a captive chimpanzee (Dehghan et al, 2013b). Other examples of likely recombination between genomes of NHP AdVs and HAdVs are represented by SAdV-35.1 (from captive chimpanzee) and SAdV-35.2 (from captive bonobo) sharing high sequence similarity with HAdV-21 and HAdV-16 .…”
Section: Introductionmentioning
confidence: 99%
“…These viruses are nonenveloped with an icosahedral capsid and contain a linear, double-stranded DNA genome of 34 to 36 kb. The recent completion of whole-genome sequencing and analysis for all prototype HAdV genomes (6) has contributed to renewed understanding of the role of homologous recombination in the evolution of HAdVs, particularly species D, but also other HAdV species (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Genes for the three major capsid proteins, the hexon, penton base, and fiber, all readily recombine among viruses within HAdV-D (13,(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%